Penerapan Model Pembelajaran Problem Base Learning (PBL) dalam Pembelajaran Fisika - Ismatulloh, Kholida; Ropikoh, Ropikoh; Marfuatun, Marfuatun (Universitas Hamzanwadi, 2023)
A study entitled the application of the PBL (Problem Base Learning) learning model to the physics learning outcomes of class VIII students at SMPN 3 Selong has been carried out. This study aims to see whether there is an influence of the PBL (Problem Base Learning) learning model on student learning outcomes in the subject of style and motion in class VIII SMPN 3 Selong. This type of research is quantitative by measuring learning outcomes from the post-test results given at the end of learning. The population used in this study was class VIII, totaling 100 people. The total sampling technique took only two classes, namely class VIII A as the experimental class and class VIII B as the control class. The research hypothesis was carried out using the t test with the results obtained ?ℎ????? = 7.023 > ?????? = 1.763 ?0 rejected ?1 accepted using a significant level of 5%.